Improving the Quality of Storytelling through a Language Experience Approach - Uswati, T S (KnE Social Sciences, 2018)
The aim of this study was to improve students’ speaking ability based on short storytelling competency through the implementation of a Language Experience Approach (LEA). This study adopted classroom action research (CAR). The subjects were students of grade XI at the class of Mathematics and Natural Sciences (IPA) 2 of Madrasah Aliyah Negeri (MAN) 2 Cirebon, which consisted of 43 students. The data collection techniques used in this study included questionnaires, observations, interviews, field notes, and tests. The results of this study indicated that the application of a language experience approach strategy can improve students’ storytelling. Keywords: language experience approach, speaking skills, storytelling